1988
DOI: 10.2519/jospt.1988.10.6.218
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a Reciprocal Test Protocol Performed on the Kinetic Communicator: An Isokinetic Test of Knee Extensor and Flexor Strength

Abstract: This study tested knee extensor and flexor strength using a reciprocal testing protocol on the Kin-Corn@ isokinetic dynamometer. The purposes were: 1) to identify the variability associated with subjects, repetitions, occasions, and their various interactions; 2) to express the overall measurement error in clinically relevant terms; and 3) advance a strategy for maximizing reliability while simultaneously ensuring that all major sources of measurement error are represented. Fourteen healthy women were tested o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 3 publications
6
21
2
Order By: Relevance
“…There are no studies of isokinetic dynamometry of the shoulder with which to compare. If we compare the SDDs of the present study with estimated from data on knee exion and extension of Harding et al (17) and of Stratford (18) we see higher SDDs in our study. The SDDs of these studies (17,18) ranged from 12% to 16%.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…There are no studies of isokinetic dynamometry of the shoulder with which to compare. If we compare the SDDs of the present study with estimated from data on knee exion and extension of Harding et al (17) and of Stratford (18) we see higher SDDs in our study. The SDDs of these studies (17,18) ranged from 12% to 16%.…”
Section: Discussionsupporting
confidence: 57%
“…If we compare the SDDs of the present study with estimated from data on knee exion and extension of Harding et al (17) and of Stratford (18) we see higher SDDs in our study. The SDDs of these studies (17,18) ranged from 12% to 16%. In order to improve the reliability in shoulder measurements additional measures can be considered, for example to perform an extra session.…”
Section: Discussionsupporting
confidence: 57%
“…For example, the importance of using preselected angles to measure validity and reliability is brought to light by Harding et al (7). Their study reported high reliability for knee extension peak torque (r = 0.952) but relatively low reliability for peak torque angle ( r = 0.630).…”
Section: Discussionmentioning
confidence: 99%
“…Competing variables include subject motivation, learning, hormonal fluctuation, subject positioning and stabilization, alignment o f machine axis with biological axis o f motion, and countless other factors. Harding et al (7) found that subject-occasion interaction was a significant source o f variance.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, isokinetic strength assessment was initiated at an angular velocity of 60°/s. This particular velocity has been shown to be reliable in healthy subjects 29,42 and was selected because the majority of our stroke participants had difficulty generating faster movements. If a participant was not able to achieve an angular velocity of 60°/s, 30°/s was used for that specific joint for both limbs at test session one and two.…”
Section: Test Protocolmentioning
confidence: 99%